CIRDAFRICA's role in rural development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
There is no doubt that the future of Africa lies in the development of its rural areas. Indeed, there is no need to stress that freedom without supportive economic strength, is like a house without walls. And it is high time that Africa seriously...